Evaluation of Lipid-Lowering Effects of Atorvastatin on Obese Patients Attending A Tertiary Healthcare Facility - Ajulo , M. O.; Ajulo , H.O.; Agbo , O. K. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Introduction: Hyperlipidemia is a major cause of atherosclerosis and atherosclerosis-associated conditions, such as coronary heart disease (CHD), ischemic cerebrovascular disease (CVD), and peripheral vascular disease. This is a progressive observational study which involved five obese participants on atorvastatin 10 mg daily and five obese participants who were not on atorvastatin who served as control group. A 3 ml blood sample was collected from the participants at recruitment and the participants were followed up after 30 days with another blood collection. The participants on atorvastatin had been adherent to drug before blood collection. The control participants were not taking any drug which lower serum cholesterol. The obtained blood samples were analysed in the laboratory for lipid profile parameters such as total cholesterol (TC), triglyceride (TG), high density lipoprotein (HDL), low density lipoprotein (LDL) and very low density lipoprotein (VLDL) by using TC, HDL and TG kits made by Randox. The results showed that the follow-up participants on atorvastatin had lipid profile of TC, TG, HDL, LDL and VLDL as 5.14±0.87 mmol/l, 1.72±0.32 mmol/l, 1.12±0.23 mmol/l, 3.24±0.79 mmol/l and 0.77±0.12 mmol/l respectively. The results for the follow-up control participants showed that TC, TG, HDL, LDL and VLDL were 4.76±0.76 mmol/l, 1.52±0.55 mmol/l, 1.15±0.15 mmol/l, 2.92±0.75 mmol/l and 0.68±0.25 mmol/l respectively. Comparison of the lipid profile of participants on atorvastatin and the control group showed that there was no significant variation in LDL (p= 0.435) at first phase and LDL (p= 0.523) at second phase respectively. There was no significant variation in reduction of LDL between the participants on atorvastatin and the control participants.